Insolvency and debt restructuring in Islamic finance: the need for a comprehensive model law - Oseni, Umar Aimhanosi (The Malaysian Current Law Journal, 2014)
This paper examines insolvency and debt restructuring in Islamic finance and the need for a comprehensive model law. The paper is organised into six major sections. The next section,which is the second, gives a brief conceptual framework of bankruptcy and financial distress in Islamic law. The third section examines the transposition of Shariah rules on bankruptcy as recognised in the classical fiqh from the individual to corporate institutions with corporate personalities. The fourth section dilates on existing bankruptcy laws in some GCC countries involving national and cross-border bankruptcies including the recently issued AAOIFI Shariah Standard on bankruptcy. The fifth section gives some case studies on debt restructuring and the need to adopt best practices such as dispute management recognised in the classical fiqh to address issues relating to defaults and looming bankruptcies in the Islamic finance industry. Finally, the sixth section gives the conclusion with some recommendations.